Rural Governmentality in Alberta: A Case Study of Neoliberalism in Rural Canada - Hallstrom, Lars (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2018)
Rural communities in Canada have faced a long history of capital and labour flight, resource extraction, and political marginalization. At the same time, despite decades of efforts toward rural development and economic/social diversification, there is little evidence of change or improved resilience in rural Canada. This article seeks to examine this lack of change against the backdrop of that developmental history, and the underlying logics that have informed rural policy-making. Focusing on Alberta, this paper argues that rural communities face a third phase of developmental approaches embedded within a neoliberal governmentality, one that emphasizes equality of opportunity, competition, capacity-building, and collaboration. This approach is simultaneously situated within a broader neoliberal objective of defining both citizens and rural communities as economic actors. In turn, this article examines the scope, scale, and role of energy and agricultural investments as a demonstration of how neoliberal governmentality structures not only how rural development is framed, but constructs economic agency for rural communities as “the only game in town” for the very populations that bear the costs. As a result, the historical failure of rural development is unlikely to change, yet, rather than be understood as problematic, will increasingly be seen as a failure on the part of rural communities themselves.